"Kontynenty" a Dedecius - Śmieja, Florian (Tematy i Konteksty, 2011)
The monthly periodical „Kontynenty” was a publication of Polish young exiles in London after the Second World War appearing from 1958–1966. In the April 1959 issue of its predecessor called “Nowy Merkuriusz” the appearance in Germany of an anthology of Polish lyric poetry by Karl Dedecius entitled “Lektion der Stille”was announced. Very soon, in June 1959 we published the earliest details of Dedecius’s curriculum vitae and furthermore an interview with the translator having secured his answers to questions written in Polish to questions put to him by Florian Smieja who collaborated with the anthology. The July–August 1962 number of “Kontynenty” called Dedecius an extraordinary translator as important as Boy. His success with Lec was recognised and translations of his theories of translating were published. Finally, Jan Brzekowski in June 1965 wrote a thorough and comprehensive review of the Polish poets published in Dedecius’s enlarged anthology.